Politik Kultural KH. Abdurrahman Wahid Dalam Demokratisasi - Subaidi Subaidi (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2014)
Cultural politics can be used as an alternative to the institutionalization of democracy in the country that has a pluralistic nation such as Indonesia. Gait Abudurrahman KH Wahid can be recognized as part of a form of cultural politics, and one of the figures that reveal the process of democratization. Cultural politics shows that democratization as an expression of resistance an actor (agency) within the structure of power through discursive and controversial actions in the space of democracy, the cultural sphere (cultural fields) and the political sphere (political fields) into the arena game (site of the struggles and strategies), which included a scramble and fight a variety of capital (cultural capital, political capital) of the figure, the political elite in power structures in changing or maintaining a doxa. Owned capital determines the style of the game, the success or failure in the race and capital exchange. This can be seen in the reproduction of discourse conducted by Gus Dur in changing doxa.